AIEgens for dark through-bond energy transfer: design, synthesis, theoretical study and application in ratiometric Hg2+ sensing. Issue 3 (1st December 2016) - Chen, Yuncong; Zhang, Weijie; Cai, Yuanjing; Kwok, Ryan T. K.; Hu, Yubing; Lam, Jacky W. Y.; Gu, Xinggui; He, Zikai; Zhao, Zheng; Zheng, Xiaoyan; Chen, Bin; Gui, Chen; et al.
Abstract : A novel dark through-bond energy transfer (DTBET) strategy is proposed and applied as the design strategy to develop ratiometric Hg 2+ sensors with high performance. Abstract : A novel dark through-bond energy transfer (DTBET) strategy is proposed and applied as the design strategy to develop ratiometric Hg 2+ sensors with high performance. Tetraphenylethene (TPE ) derivatives with aggregation-induced emission (AIE) characteristics are selected as dark donors to eliminate emission leakage from the donors. The TBET mechanism has been adopted since it experiences less influence from spectral overlapping than Förster resonance energy transfer (FRET), making it more flexible for developing cassettes with large pseudo-Stokes shifts. In this work, energy transfer from theTPE derivatives (dark donor) to a rhodamine moiety (acceptor) was illustrated through photophysical spectroscopic studies and the energy transfer efficiency (ETE) was found to be up to 99%. In the solution state, no emission from the donors was observed and large pseudo-Stokes shifts were achieved (>280 nm), which are beneficial for biological imaging. Theoretical calculations were performed to gain a deeper mechanistic insight into the DTBET process and the structure–property relationship of the DTBET cassettes. Ratiometric Hg 2+ sensors were rationally constructed based on the DTBET mechanism by taking advantage of the intense emission ofTPE aggregates. The Hg 2+ sensors exhibited well resolved emission peaks. >6000-fold ratiometric fluorescent enhancement is also achieved and the detection limit was found to be as low as 0.3 ppb. This newly proposed DTBET mechanism could be used to develop novel ratiometric sensors for various analytes and AIEgens with DTBET characteristics will have great potential in various areas including light harvesting materials, environmental science, chemical sensing, biological imaging and diagnostics.